Play practice engaging and developing skilled players from beginner to elite - Launder, Alan G. (Human Kinetics, 2013)
Offers an innovative approach to teaching and coaching sport that combines contemporary theory with the experience of practical and reflective work in real sport environments. It covers a wide range of team and individual sports, including archery, table tennis, flag football, skiing, cricket and track and field.